Portfolio Efficiency Analysis of JAPFA and Indofood CBP Using the Efficient Frontier Approach: Implications for Food Sector Policy - Yuliani, Poppy; Pamungkas, Bagus; Albart, Nicko (Journal Research of Social Science, Economics, and Management, 2025)
The Indonesian capital market, particularly the food sector, is undergoing significant changes due to strategic government policies such as the free lunch program, which directly influence market dynamics and investor behavior. This study addresses the problem of how investors can optimize portfolio efficiency between two dominant food sector stocks, JAPFA and Indofood CBP (ICBP), under regulatory uncertainty. The primary objective is to identify an optimal portfolio allocation that balances risk and return using the Efficient Frontier approach developed by Markowitz (1952). Employing a quantitative descriptive method, daily stock price data from January to December 2024 were analyzed to simulate portfolio weights, expected returns, and risks. Results reveal a very low correlation (0.085) between JAPFA and ICBP, indicating strong diversification benefits that minimize portfolio risk without sacrificing returns. An optimal portfolio allocation around 30% JAPFA and 70% ICBP is recommended to maximize investment efficiency. The study’s findings have important implications for investors, portfolio managers, and policymakers by demonstrating how diversification in the food sector can hedge against market volatility driven by government interventions. This research enriches the literature on portfolio management by integrating policy-driven market conditions. Future research should explore multi-asset portfolios, incorporate macroeconomic factors, and apply advanced optimization techniques such as artificial intelligence to better navigate complex and evolving market environments.